MOTIVATION FACTORS FOR WOMEN TO BECOME AN ENTREPRENEUR AND CONTRIBUTE TO SOCIAL INNOVATION - Isma Addi, Jumbri; Zahir Zainudin, Mohamad; Mohamad Sharif, Sabri; Muhd Feisal Ismail, Albert Feisal@ (Journal of Human Capital Development (JHCD), 2019)
This paper attempts to examine the motivational factors attached to women to become entrepreneurs and contribute to social innovation related to small and medium enterprises (SMEs), particularly in Melaka. The need theory was used as a theoretical framework to study the motivation of women to become an entrepreneur and contribute to social innovation. A survey research design involving the use of questionnaires and structured interviews were adopted to obtain primary data. There are 200 women entrepreneurs currently engaged in their businesses in Melaka. This study concludes that women entrepreneurs are motivated by a high need for achievement, a slight high need for power and a moderate need for affiliation. The paper also sheds some light to women entrepreneurship in emerging economies and recommends having more initiatives to encourage and develop women entrepreneurs to contribute to social innovation for the success of Malaysia's economy.